Journal of Ancient History (De Gruyter, 2013)
The Journal of Ancient History aims to provide a forum for scholarship covering all aspects of ancient history and culture from the Archaic Period to Late Antiquity (roughly the ninth century BCE through the sixth century CE). The journal publishes peer-reviewed articles concerning the history and historiography (ancient and modern) of the ancient Mediterranean world and of neighboring civilizations in their relations with it.